2020
DOI: 10.1002/tesj.519
|View full text |Cite
|
Sign up to set email alerts
|

An implementation of project‐based learning in an EFL context: Japanese students’ and teachers’ perceptions regarding team learning

Abstract: Project‐based learning (PjBL) has demonstrated its ability to improve a range of skills in students. However, some studies have reported that English teachers have difficulty activating interaction among all the participants, teachers and students, in a PjBL practice. No studies have empirically investigated how teachers can collaborate in PjBL and how students can engage in interactive learning activities. Therefore, this research demonstrates a PjBL practice led by the notion of value‐centered team learning.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The effects of Project-based Learning on writing classes have been argued widely. Many research found that this strategy could improve learners' writing skills (Alotaibi, 2020;Lu, 2021;Qing, 2019;Yamada, 2021). Besides, it also could enhance students' creativity, participation, and self-reliance (Aghayani & Hajmohammadi, 2019;Alotaibi, 2020;Ismuwardani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The effects of Project-based Learning on writing classes have been argued widely. Many research found that this strategy could improve learners' writing skills (Alotaibi, 2020;Lu, 2021;Qing, 2019;Yamada, 2021). Besides, it also could enhance students' creativity, participation, and self-reliance (Aghayani & Hajmohammadi, 2019;Alotaibi, 2020;Ismuwardani et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Strategies for managing time effectively, streamlining assessment processes, and maintaining student motivation are essential for mitigating the burdensome nature of PBL in EFL contexts and inspiring teachers to deal with these challenges for their students' learning. Students' attitudes and language proficiency are the result of the complex interplay between individual differences, instructional approaches, and the cultural context in implementing PBL in EFL classrooms (Baghoussi & El Ouchdi, 2019;Yamada, 2020;Ram, 2022;Maqbulin, 2023;Zhong, 2023). Implementing thoughtful strategies to motivate students, effectively scaffold language learning, and create inclusive and supportive learning environments conducive to PBL is vital.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, studies have also been conducted on collaborative learning components and their impact on EFL students in diverse contexts. For instance, Yamada [48] examined a project-based learning approach guided by value-centered team learning. Nineteen teachers and 73 Japanese high school students completed a year-long project-based learning program.…”
Section: Previous Studiesmentioning
confidence: 99%